Qualitative Dermal Exposure Assessment of Laboratory Technicians in Selected Chemical Laboratories in Eastern Province, Saudi Arabia - Ayman M. Arfaj; Jose Lauro M. Llamas (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The assessment of dermal exposure is a complex task. The most commonly used methods have fundamental problems, and there are large gaps in the documentation and validation of the known assessment methods. This study aimed to determine the prevalence of self-reported skin problems in laboratory technicians. Additionally, to determine if there is an association between self-reported skin problems and work tasks and other exposure-related parameters, we developed a simple qualitative questionnaire that may be used for conducting qualitative dermal exposure assessments. Methods: A well-structured survey questionnaire was developed and 45 laboratory technicians were interviewed while conducting qualitative dermal exposure assessments in three selected laboratories. The sampling technique was a qualitative survey conducted through interviews. The examined variables included skin problems, work characteristics, and chemicals used. Results: This study indicated that 18% of technicians reported having skin problems, most notably inexperienced technicians or technicians with more than 6 years of experience. Skin problems were also identified in technicians who worked between one and eight hours, performed manual operations, and handled solvents. The prevalence of skin problems has also been associated with changing gloves. However, no significant differences were observed between the examined parameters and skin problems (p > 0.05). Conclusion: The prevalence of self-reported skin problems (18%) among laboratory technicians was not high. The prevalence of dry skin was low (11%). A well-structured questionnaire can be used to conduct a qualitative dermal risk assessment. As this was a cross-sectional study with a small sample size, it was not possible to establish a causative effect between exposure to workplace hazards and dermal problems.